INITIATING A PERMANENT ELECTORAL BODY TO RESOLVE DIGNIFIED ELECTION DISPUTES: ASSESSING THE EFFECTIVENESS OF GAKKUMDU - Fitria Esfandiari; Sholahuddin Al Fatih (Faculty of Law, Universitas Sebelas Maret, 2020)
This study aimed to evaluate ineffectiveness in the process of resolving electoral disputes through Gakkumdu in simultaneous elections in 2019. However, in practice there are difficulties in handling the consequences of criminal norms and technical rules which are not clearly formulated, causing differences of opinion in resolving election disputes. The approach method used by the author with normative juridical approach method (legal Research) through literature study using primary legal data namely Law Number 7 of 2017 on Elections, KPU Regulation and Court Decision related to elections. Secondary data, especially library materials containing information about election dispute problems through Gakkumdu. The collection of legal materials is carried out by tracing the library in the form of information about the evaluation of gakkumdu's role in resolving the dispute of the 2019 Elections and in analysis using the method of descriptive analysis. The results of this study concluded that Gakkumdu which is an organ formed based on the mandate of Law Number 7 of 2017 on Elections, has not worked optimally. It is very vulnerable to overlap of authority between Bawaslu, The Police and the Prosecutor's Office. On the other hand, this organ has the opportunity to reduce the authority and independence of Bawaslu, which has been supervising the elections. The combination of the three institutions organically and substantive has not been able to parse the dispute of the 2019 elections.